Sarcoidosis and Purified Protein Derivative reactivity - Hofland, Regina W; Thijsen, Steven FT; Bouwman, John; van der Wel, Myrtle; Bossink, Ailko WJ (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2014)
Background: The possible association between (tuberculous and nontuberculous) mycobacterial infections and sarcoidosis is still a matter of dispute. Using diagnostic tests for specific T-cell responses, this association can be investigated in an innovative manner. Objective: To measure the T-cell responsiveness to the purified protein derivative (PPD) antigen in blood and broncho-alveolar lavage (BAL) fluid in patients with sarcoidosis and patients with other causes of interstitial lung disease. It was hypothesized that if a mycobacterial infection of the lung is of importance for the development of sarcoidosis, T-cell responsiveness towards the PPD antigen would be increased in patients with sarcoidosis when compared to patients with other causes of interstitial lung disease. Methods: A single-center study was conducted which included patients with and without sarcoidosis. Venous blood was collected and BAL was performed for, inter alia, Interferon Gamma Release Assay´s (IGRA) with different stimulating antigens, including PPD, ESAT-6, CFP-10 and, as a control, Epstein-Barr virus (EBV). Results: A total of 118 patients were included. There is no difference between PPD reactivity in BAL fluid in patients with or without sarcoidosis. In patients without sarcoidosis, ELISpot PPD in blood shows more reactivity compared to patients with sarcoidosis, although this difference is not significant. ELISpot EBV and TB results are not significant different between both groups. Conclusion: These results provide no evidence for the involvement of different mycobacteria in the pathogenesis of sarcoidosis.